2020
DOI: 10.3389/fpsyg.2020.546546
|View full text |Cite
|
Sign up to set email alerts
|

Taking Risks With Cybersecurity: Using Knowledge and Personal Characteristics to Predict Self-Reported Cybersecurity Behaviors

Abstract: Individuals’ use of insecure cybersecurity behaviors, including the use of weak passwords, is a leading contributor to cybersecurity breaches. While training individuals on best practices in cybersecurity continues to be implemented, prior research has found that training people in the use of secure passwords has not proven to be effective. Developing profiles of individual who are likely to become victims of password hacking, phishing scams, and other types of breaches would be useful, as they could be used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 63 publications
0
22
0
1
Order By: Relevance
“…In another recent study, findings suggested that not only were riskier CS behaviors highly related to CS breaches in general, but that training to increase the use of best practices such as password complexity did not effectively compensate for the problematic behavior. 28 In this study, significant findings related primarily to one's proficiency and competence could also represent a hidden risk in that scores suggestive of greater competence may result from a desire to appear more competent about CS than the respondent actually is. Another result that seems to have particularly salient implications is that perceived severity and perceived experience were the strongest predictors of perceived vulnerability.…”
Section: Discussionmentioning
confidence: 78%
“…In another recent study, findings suggested that not only were riskier CS behaviors highly related to CS breaches in general, but that training to increase the use of best practices such as password complexity did not effectively compensate for the problematic behavior. 28 In this study, significant findings related primarily to one's proficiency and competence could also represent a hidden risk in that scores suggestive of greater competence may result from a desire to appear more competent about CS than the respondent actually is. Another result that seems to have particularly salient implications is that perceived severity and perceived experience were the strongest predictors of perceived vulnerability.…”
Section: Discussionmentioning
confidence: 78%
“…Recently, a study by Kannison and Chan-Tin [45] found a relationship between psychological features and safety behaviors, therefore confirming the relevance of the human component in the implementation of safety behaviors.…”
Section: Behavior Analysis: a Primermentioning
confidence: 75%
“…, keeping anti-virus software up to date). Meanwhile, Kennison & Chan-Tin (2020) reported rather different results: extraversion, agreeableness, and emotional stability -not openness nor conscientiousness- explain why some users are prone to commit risky cyber behaviors ( e.g. , not signing out of a shared computer, sharing password with someone else) while others are not.…”
Section: Theoretical Frameworkmentioning
confidence: 98%